Análisis de la propuesta “Educa Radio” como recurso didáctico para los docentes de la educación básica elemental - Älvarez Cedeño, Eilin Nicole (2018)
The native radio of orality, in the convergence of multimedia languages and hypertextuality continues in the journey of educating, informing and entertaining. The radio mean is conceived as an important educational agent; nevertheless, there is a marked tendency to consider the mass media and with them the radio as a distracting instrument and media manipulation. In the Ecuadorian social context and in many other countries in Latin America, actions have been undertaken so that the media can develop educational content that favors formal and informal learning processes. In the Ecuadorian case, it is mainly due to the implementation of laws and regulations in the field of communication. From this handle the present study analyzes the proposal of “Educa Radio”, strip destined to fulfill with the stipulated on article 74 of the Organic Law of Communication, with respect to the denominated educational hour in audio-visual means. The research is addressed from the duality that exists between communication and education, considering the theoretical and practical component of these disciplinary areas to recognize the strength of “Educa radio”, as a didactic resource for teachers specifically at the elementary level of basic education.